Pertumbuhan Morfologi Bibit Kelapa Sawit Pre Nursery dengan Penanaman Secara Vertikultur - Vira Irma Sari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Verticulture is a vertical planting technique. This method never used for annual plant like oil palm seedlings. The physical condition of oil palm roots that still has short roots could be planted in verticulture system. The objectives of this research are: 1) to obtain alternative technique for planting of oil palm seedlings uses verticultur system; 2) to know the effect of verticultur system for oil palm seedlings in pre nursery; and 3) to know the method of making vertical shelf and watering using pump for oil palm seedlings in pre nursery. The research conducted at Teaching Farm II of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi on February to July, 2018. The treatment was arranged in non factorial randomized block design with four replication and two treatment. First treatment is verticultur system (planting in vertical with pipe) and the second is planting horizontally (conventionally, using glass cup). There are 4 vertical shelves, and one shelves has 40 oil palm seedlings, so there are 160 seedlings that plant vertically. The number of oil palm seedlings in vertical shelves as same as in horizontal planting. The total number of seedlings are 320 seedlings. Data were analyzed in analysis of variance and continued by Duncan Multiple Range Test (DMRT). The result showed that: 1) verticultur system could be alternative method for oil palm seedling in pre nursery; 2) the application of verticultur system not significantly effect for morphological parameters, however based on physical observation, the morphological of seedlings that planted vertically is better than horizontal planting; and 3) the making of vertical shelves are made by arranging vertical paralon pipes on metal shelves, and installing ponds and water pumps under the shelves for watering oil palm seedlings.